THE IMPACT OF WOM (WORD OF MOUTH) ON THE BUYING PROCESS OF ONLINE COSMETICS AMONG FEMALE COLLEGE STUDENTS IN YOGYAKARTA - Yuni Retnowati (Nusantara Hasana Journal, 2022)
Word of Mouth Communication (WOM) is a way of communication that delivers personal information and product recommendations. This study seeks to: (1) describe how word-of-mouth influences the decision-making process of Yogyakarta female students to purchase cosmetics online; and (2) determine what criteria lead Yogyakarta female students to purchase cosmetics online. Determine which direction WOM or e-WOM has a greater impact on Yogyakarta female students when purchasing cosmetics online, and (3) identify the characteristics that lead Yogyakarta female students to purchase cosmetics online. This sort of qualitative research collects data by observation, surveys of up to 160 individuals, and interviews with up to 30 individuals. Purposive sampling was used to identify informants, and descriptive analysis was performed on the data. The findings of this study demonstrate that WOM effects purchasers' cognition and emotion, resulting in product purchasing behavior. The experience of a satisfied friend (51 percent), discounted prices (24 percent), online consumer testimonials (17 percent), and attractive marketing are the variables that impact the online purchase of cosmetic items by students in Yogyakarta (8 percent ). WOM has a direct impact on female students' online cosmetic purchase decisions. Word-of-mouth influences the online purchase of cosmetics, therefore consumer satisfaction plays a significant role in cosmetics purchasing decisions.